2016
DOI: 10.2147/cia.s116185
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of quality of life in chronic, progressing rheumatic diseases based on the example of osteoarthritis and rheumatoid arthritis 

Abstract: BackgroundRheumatic diseases, irrespective of etiology and clinical course, influence different areas of a patient’s life. Adapting to disability and limitations caused by an illness is very difficult for many patients. The main goal of a therapeutic procedure should be improvement of health-related quality of life (QoL).ObjectiveEvaluation of the factors that influence the QoL that are conditioned by the state of health of patients with osteoarthritis (OA) and rheumatoid arthritis (RA).MethodsThe study group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 20 publications
1
18
1
2
Order By: Relevance
“…[17][18][19][20][21][22][23][24] The lower number of points in the PCS domain in comparison to the MCS domain may indicate that RA affects more the physical than the mental sphere as indicated by other authors. 21,23,24 It was also shown that the quality of life of patients with RA depends on many factors of physical, mental and social functioning sphere.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[17][18][19][20][21][22][23][24] The lower number of points in the PCS domain in comparison to the MCS domain may indicate that RA affects more the physical than the mental sphere as indicated by other authors. 21,23,24 It was also shown that the quality of life of patients with RA depends on many factors of physical, mental and social functioning sphere.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24] The lower number of points in the PCS domain in comparison to the MCS domain may indicate that RA affects more the physical than the mental sphere as indicated by other authors. 21,23,24 It was also shown that the quality of life of patients with RA depends on many factors of physical, mental and social functioning sphere. 17,[19][20][21][23][24][25][26][27][28][29][30][31] Studies conducted by many authors have shown that poorer functioning of the respondents in the physical sphere is conditioned by the duration of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 The common clinical features of OA include joint pain, swelling, stiffness and crepitation, with loss of joint function that results in a reduced quality of life in patients. 3 In approximately 12% of patients, OA may be secondary to an underlying condition, including prior joint injury, abnormal mechanical loading (i.e. bowed legs), an inflammatory arthropathy such as gout, and metabolic conditions such as diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, when Systemic Lupus Erythematosus is active, it may course with kidney failure, myocarditis and seizures, which can lead to death, but also compromise short and long-term functionality and quality of life. Rheumatoid Arthritis, on the other hand, poses less life-threatening complications, but is one of the most limiting rheumatologic diseases 17 . It is also important to stress that accessible specific therapeutic targeting molecular structures are not available 18 .…”
mentioning
confidence: 99%